District Recreation activity of Health Promotion happily Aging in Boleklong subdistrict Long district Phrae province - ธรรมกวินวงศ์ ณัฐกฤษฏ์; มาทา ฉัตรสุดา (Journal of The Royal Thai Army Nurses, 2019)
In a district recreation activity of health promotion happily aging in Boleklong subdistrict Long district Phrae province, the participation of elderly in extended recreation and comparative of happy aging are studied and a program recreation activity of health promotion is developed. The research has a mixed methodology to perform qualitative research by focus group discussion and quantitative research by true experimental design, Pretest-Posttest control group design and analyzed by a Pair t-test and thematic analysis. Results: After participations of the elderly in program recreation activity of health promotion. Total participation average score were 4.05. The happiness of aging after participation to develop program recreation activity of health promotion is significant at .05. The program recreation activity of health promotion has 4 components 1) Handicrafts recreation was a hand-on activity with stretch finger and creating career of family and community 2) Matrix of nine squares training applied in five step dancing of Boleklong district including Saongam, Yokkhao, Sabadmee, Tumbit, Keangtawan 3) Songs and play folk music of Boleklong district, i.e. Joy song, Kaow song, Ramwongkongka song. 4) Story telling of Good health history, Culture, Traditions and Occupation. Conclusion: Program recreation activity of health promotion aging of Boleklong district was developed by participation process and can be used as a model for other communities.